Analysis of Mathematical Problem Solving Ability Viewed from Student Learning Style - Febrina, Helmi; Hali, Fitriyani (Universitas Sembilanbelas November Kolaka, 2020)
This study aims to describe mathematical problem solving abilities in terms of student learning styles. This type of research is descriptive qualitative. The subjects of this study consisted of 24 students of class IX SMP Negeri 16 Konawe Selatan. The research instruments used were: (1) mathematical problem solving ability test questions, (2) interviews, (3) learning style questionnaires. The results obtained information that: (1) From 24 students of class IX SMP Negeri 16 Konawe Selatan obtained information that there are 5 students who have high category mathematical problem solving ability with a percentage of 20.83%. There are 2 students who have the ability to solve mathematical problems in the medium category with a percentage of 8.33%. and as many as 17 students with low category mathematical problem solving abilities with a percentage of 70.83%. (2) The unimodal learning style is dominated by the auditory type as many as 8 students with a percentage of 33.33%, then the visual type as many as 2 students with a percentage of 8.33%, and read/write as many as 1 student with a percentage of 4.17%. Meanwhile, the multimodal learning styles identified in the study were bimodal learning styles consisting of 5 students with a percentage of 20.83%, A-R with a percentage of 2 students with a percentage of 8.33%, A-K with 1 student with a percentage of 4.17%, trimodal learning styles with only A-R-K types as many as 2 students with a percentage of 8.33%, and a quadmodal learning style there is V-A-R-K as many as 3 students, with a percentage (12.50%). (3) The mathematical problem solving ability of students with unimodal learning style Visual (V), Auditory (A) is in the low category and the type of Read/write (R) is in the medium category, mathematical problem solving abilities of students with bimodal learning style type A-R and A-K are in the low category while the V-K type is in the medium category, the mathematical problem solving ability of students with trimodal learning style type A-R-K is in the low category, and mathematical problem solving abilities of students with quadmodal learning style are V-A-R-K (visual-auditory-read/write- kinesthetic) is still in the low category.